Clinical Outcome and Surgical Outcome of Moyamoya Disease after Combined Revascularization Performed at the Neurological Institute of Thailand - Yuthagovit, Sarunya; Lertbutsayanuku, Punjama; Tirakotai, Wuttipong (Asian Journal of Neurosurgery, 2024)
Objective Moyamoya disease is a chronic, progressive, intracranial steno-occlusive disease. Cerebral revascularization has proved that it is more beneficial than medical therapy for prevention of recurrent stroke. We aimed to report clinical and surgical outcome of moyamoya disease after combined revascularization in Thai population.Materials and Methods From October 2015 to March 2023, patients diagnosed with moyamoya disease and were operated with combined revascularization were included. Patients were evaluated for hemodynamic state with preoperative and postoperative blood oxygenation level-dependent magnetic resonance (BOLD MR) imaging. Demographic data, serial imaging, surgical outcome, and clinical outcome were analyzed. Morbidity and mortality rates of surgery were reported. For clinical outcome evaluation, modified Rankin Scale (mRS) scores were compared between preoperative and postoperative outcome. The mRS score of 0 to 2 signify good outcome after surgery.Results There were a total of 55 patients. Ischemic stroke was the most common presentation (87.3%). Based on the Suzuki's classification, most of the patients were stage 3 and 4. Clinical outcome measured with mRS score had good outcome, 100% (mRS score 0–2). For surgical outcome, overall graft patency was 94.8%, overall complication rate was 6.5%, and mortality rate was zero. Mean follow-up duration was 44.5 ± 25.1 months. Recurrent stroke occurred in 1.3%, which was recurrent ischemic stroke.Conclusion Combined revascularization in moyamoya disease in the Thai population has a good clinical outcome, an acceptable risk of complication, and a reduced recurrent rate of stroke. Clinical and surgical outcome should be studied in the long term with the use of BOLD MR with carbon dioxide stimuli for the evaluation of cerebral blood flow in the patient.
Keywords: BOLD MR; clinical outcome; combined revascularization; moyamoya disease; surgical outcome; Thai population